Little Innovation Engines That Could: Expanding Beyond Traditional Economic Development - Young, Tara (Rural Telecommunications, 2019)
'7 don't want to use my creative energy on someone else's user interface. "-Jeff Bezos, Founder of Amazon Google and Amazon both used a garage filled with friends from Stanford, Facebook needed a Flarvard dorm room, and writer Virginia Woolf opted for a private room in her house within the artistic enclave of Bloomsbury. The more common historical approach utilizes a county, regional or super-regional office of economic development to recruit larger, established businesses to a community hoping they'll be an anchor as a keystone employer. INNOVATION ENGINES At the interseotion cf th s paradigm shift and the resources reeded to make it happen is the rural telco, fii ing the role of the innovation engine, the connectior point, and in many cases, the provider of the space and technology needed for 21st century innovation. The co-op and its users benefit by having these "senior interns" providing training on plasma cutters and other pieces of equipment in their fabrication lab or by having them act as docents during their youth Coding Dojo classes.